Tree Mortality: Testing the Link Between Drought, Embolism Vulnerability, and Xylem Conduit Diameter Remains a Priority - Anfodillo, Tommaso; Olson, Mark E. (Frontiers in Forests and Global Change, 2021)
Global climate change-induced droughts are provoking events of forest mortality worldwide, with loss of tree biomass and consequent ecosystem services. Ameliorating the effects of drought requires understanding the causes of forest mortality, with failure of the hydraulic system being an important contributor. Comparative anatomical data strongly suggest that, all else being equal, wider conduits are more vulnerable to drought-induced embolism than narrow ones. However, physiology experiments do not provide consistent support for such a link. If a vulnerability-diameter link exists, though, it would contribute not only to explaining and predicting forest mortality but also to interventions to render individual trees more drought resistant. Given that xylem conduits scale with plant height, taller plants have wider conduits. If there is a vulnerability-diameter link, then this would help explain why taller plants are often more vulnerable to climate change-induced drought. Links between conduit diameter, plant height, and vulnerability would also provide guidance for standardizing sampling of hydraulic variables across individuals and suggest that selecting for relatively narrow conduits at given height from the tree top could produce more drought resistant varieties. As a result, given current ambiguities, together with the potential importance of a link, it is important to maintain the vulnerability-diameter link as a research priority.